Present‐Day Stress Field Influences Bedrock Fracture Openness Deep Into the Subsurface. Issue 23 (26th November 2020) - Moon, Seulgi; Perron, J. Taylor; Martel, Stephen J.; Goodfellow, Bradley W.; Mas Ivars, Diego; Hall, Adrian; Heyman, Jakob; Munier, Raymond; Näslund, Jens‐Ove; Simeonov, Assen; Stroeven, Arjen P.
Abstract: Fracturing of bedrock promotes water‐rock interactions and influences the formation of the life‐sustaining layer of soil at Earth's surface. Models predict that present‐day stress fields should influence bedrock fracture openness, but testing this prediction has proven difficult because comprehensive fracture data sets are rarely available. We model the three‐dimensional present‐day stress field beneath the deglaciated, low‐relief landscape of Forsmark, Sweden. We account for ambient regional stresses, pore pressure, topography, sediment weight, and seawater loading. We then compare the modeled stresses to a data set of 50, 000 fractures reaching depths of 600 m at Forsmark. We show that modeled failure proxies correlate strongly with the fraction of observed open fractures to depths of 500 m. This result implies that the present‐day regional stress field, affected by surface conditions and pore pressure, influences fracture openness in bedrock hundreds of meters beneath the surface, thereby preparing the rock for further weathering. Plain Language Summary: The "critical zone"—the life‐sustaining part of the Earth that extends from the top of the tree canopy to the bottom of permeable bedrock—is essential for ecosystems and agriculture. The opening of bedrock fractures and onset of water‐rock interaction are crucial to the formation of the critical zone. Within the bedrock, the intensities of horizontal regional forces and vertical gravitational forces typically increase with depth. These force intensities, or stresses, are modified by surface effects associated with topography, the weight of overlying seawater and sediment, and by groundwater pressure. However, the influence of these surface effects on fractures has been difficult to observe because comprehensive fracture data sets are rare. In this study, we examine whether, and to what depths, bedrock may fracture under the influence of stress associated with surficial conditions. We compare bedrock stress calculations with 50, 000 fractures from 18 cores reaching depths of 600 m at Forsmark, Sweden. We find that the present‐day stress field influences the opening of fractures to depths of 500 m, contributing to the formation of the critical zone and the preparation of rock for weathering hundreds of meters beneath the surface, much deeper than previously thought. Key Points: We calculate three‐dimensional present‐day subsurface stress fields in a low‐relief landscape at Forsmark, Sweden Present‐day stress fields correlate strongly with the fraction of observed open fractures in cores down to 500 m depth Subsurface bedrock stress influenced by surface conditions and pore pressure contributes to the formation of the deep critical zone